Upaya Peningkatan Pengetahuan Tentang Makanan Dan Minuman Yang Meningkatkan Tenaga Persalinan - Yadul Ulya; Siskha Maya Herlina; Regina Pricilia Yunika (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The success of maternal health efforts can be seen from the indicators of the Maternal Mortality Rate (MMR). MMR is the number of maternal deaths during pregnancy, childbirth, and postpartum caused by pregnancy, childbirth, and postpartum or their management. Long parturition and bleeding are very important problems that have not been resolved until now, even making a big scourge in the world of obstetrics. Where the delivery process greatly affects the quality of the baby born. Fluid and nutritional needs (eating and drinking) are physiological needs that must be met properly by the mother during the delivery process. During the labor process, mothers need stamina and excellent body condition, therefore consuming nutritious food before delivery is very important. The use of foods and beverages that can increase energy during labor must be supported by comprehensive information so that it has a beneficial effect. Therefore, it is necessary to conduct health education about food and beverages that increase the labor force in labor. The activity of providing health education about food and drink that increases the labor force was carried out in Jempong Baru Village, Sekarbela District, Mataram City, and was attended by 12 pregnant women. The results of the pretest and posttest showed that there was an increase in knowledge of pregnant women about food and drink which increased labor power